Measurement of electromyography during bobsleigh push-start: A comparison with world top-ranked athletes - Park, S.-H.; Lim, S.-T.; Kim, T.-W. (Science & Sports, 2019)
Aims: In the present study, we aimed to determine the muscles that mostly respond to the push-start of the sled. Methods: Seven male Korea Winter Olympics elite athletes form the two-man bobsleigh team. Performance was assessed using push-start time. Electromyogram (EMG) activity of the rectus femoris (RF), tibialis anterior (TA), gastrocnemius medialis (GM), and biceps femoris (BF) muscles was recorded during the push-start phases. Results: The paired t-test showed that right and left GM activity (P<0.001) was significantly higher in top-ranked athletes than ordinary athletes. However, no significant difference in EMG activities of the RF, TA, and BF was observed, but there was a trend toward higher BF (left) activity (P=0.066) in top-ranked athletes. Stepwise multiple regression revealed that the left (multiple r2=0.081; P<0.01) and right BF (multiple r2=0.078; P<0.01) were a significant and powerful predictor that accounted for 8.1% and 7.8% of the variance in start time, respectively. Conclusion: This study provides preliminary evidence to suggest that BF muscle activity may represent an effective push-start time to reduce race time in bobsleigh athletes.